Polyketide Intermediate Mimics as Probes for Revealing Cryptic Stereochemistry of Ketoreductase Domains - Li, Yang (ACS Chem Biol, 2014)
[Image: see text] Among natural product families, polyketides have shown the most promise for combinatorial biosynthesis of natural product-like libraries. Though recent research in the area has provided many mechanistic revelations, a basic-level understanding of kinetic and substrate tolerability is still needed before the full potential of combinatorial biosynthesis can be realized. We have developed a novel set of chemical probes for the study of ketoreductase domains of polyketide synthases. This chemical tool-based approach was validated using the ketoreductase of pikromycin module 2 (PikKR2) as a model system. Triketide substrate mimics 12 and 13 were designed to increase stability (incorporating a nonhydrolyzable thioether linkage) and minimize nonessential functionality (truncating the phosphopantetheinyl arm). PikKR2 reduction product identities as well as steady-state kinetic parameters were determined by a combination of LC-MS/MS analysis of synthetic standards and a NADPH consumption assay. The d-hydroxyl product is consistent with bioinformatic analysis and results from a complementary biochemical and molecular biological approach. When compared to widely employed substrates in previous studies, diketide 63 and trans-decalone 64, substrates 12 and 13 showed 2–10 fold lower K(M) values (2.4 ± 0.8 and 7.8 ± 2.7 mM, respectively), indicating molecular recognition of intermediate-like substrates. Due to an abundance of the nonreducable enol-tautomer, the k(cat) values were attenuated by as much as 15–336 fold relative to known substrates. This study reveals the high stereoselectivity of PikKR2 in the face of gross substrate permutation, highlighting the utility of a chemical probe-based approach in the study of polyketide ketoreductases.